67Gallium Kinetics in the Blood of Patients with Malignant Tumors - Keller, F.; Maiga, M. K.; Koeppe, P. (Nuklearmedizin - NuclearMedicine, 1983)
67GaIlium was injected into 60 patients with malignant tumors and into 42 patients in whom malignant tumors had been excluded by clinical investigation. 67Ga kinetics in blood were evaluated by non-linear least square regression computer analysis according to an open 2-compartment model where elimination proceeds from the peripheral compartment. Parameters of 67Ga kinetics in tumor patients showed a bimodal distribution, as was also the case in patients without tumors. No difference could be demonstrated between kinetic parameters of tumor patients and patients without tumors. In 4 patients, 67Ga kinetics could be evaluated before and after treatment of their malignant tumors, but a decrease in the volume of distribution was the single alteration of kinetic parameters occurring after treatment. This decrease may be explained by a smaller peripheral compartment resulting from the loss of tumor mass after treatment. Nevertheless, we conclude that the evaluation of 67Ga kinetics in blood will provide only limited information about the presence, size and growth rate of malignant tumors in man.